Preterm infant: maternal experience during breastfeeding in neonatal intensive care unit and after discharge - Leila Medeiros Melo; Márcia Maria Tavares Machado; Álvaro Jorge Madeiro Leite; Karla Maria Carneiro Rolim (Rev Rene)
The objective was to identify the perceptions and experiences in relation to maternal care during hospitalization feeding of preterm infants in the Neonatal Intensive Care Unit and after discharge. Qualitative approach, exploratory-descriptive, using semi-structured interviews, aimed to address the lived experience of eleven mothers who gave birth to their babies. The interviews were conducted in the homes of mothers, between the months of June and October 2009. Through an analysis and interpretative understanding, the results indicated difficulties inter-subjective communication with professionals and the occurrence of significant early weaning with the introduction of porridge and other foods potentially harmful to the health of preterm infants. It was clear that mothers need to be accommodated in formal advisory groups during and after hospitalization, receiving structured information about feeding practices to establish the most appropriate health care for their children.